2020
DOI: 10.3390/microorganisms8081176
|View full text |Cite
|
Sign up to set email alerts
|

A Holistic Review on Euro-Asian Lactic Acid Bacteria Fermented Cereals and Vegetables

Abstract: Lactic acid fermentation is one of the oldest methods used worldwide to preserve cereals and vegetables. Europe and Asia have long and huge traditions in the manufacturing of lactic acid bacteria (LAB)-fermented foods. They have different cultures, religions and ethnicities with the available resources that strongly influence their food habits. Many differences and similarities exist with respect to raw substrates, products and microbes involved in the manufacture of fermented products. Many of them are produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(52 citation statements)
references
References 133 publications
0
50
0
2
Order By: Relevance
“…It has been found that not all fibres are classified as prebiotics; but, most prebiotics are classified as dietary fibres (Grabitske and Slavin 2009). Prebiotics consumption, alone or with probiotics, have immense health benefits to the gut microbiota and overall health status of an individual (Ashaolu and Reale 2020; Ashaolu 2020a). Lactobacilli and bifidobacteria are primary bacteria targeted in prebiotic feeding studies.…”
Section: Dietary Fibres and Prebioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that not all fibres are classified as prebiotics; but, most prebiotics are classified as dietary fibres (Grabitske and Slavin 2009). Prebiotics consumption, alone or with probiotics, have immense health benefits to the gut microbiota and overall health status of an individual (Ashaolu and Reale 2020; Ashaolu 2020a). Lactobacilli and bifidobacteria are primary bacteria targeted in prebiotic feeding studies.…”
Section: Dietary Fibres and Prebioticsmentioning
confidence: 99%
“…Investigations on the ability of carbohydrates to be utilized by lactobacilli and bifidobacteria showed that galactooligosaccharides (GOS) and lactulose support the most favourable growth characteristics, but inulin, maltodextrin and polydextrose revealed poor growth characteristics (Slavin 2013). Generally, it is speculated that prebiotics intake will reduce the occurrence and time of infectious or antibiotic‐associated diarrhoea; reduce the swelling and signs related to inflammatory bowel disease; confer protective effects against colon cancer and cardiovascular diseases; enhance bioavailability and absorption of minerals; and improve satiety and weight loss (Ashaolu 2020b).…”
Section: Dietary Fibres and Prebioticsmentioning
confidence: 99%
“…Starters used to initiate fermentation can be either natural (e.g., backslopping), or selected commercial starters to standardize the organoleptic characteristics of the final product [20,48]. Compiling a geographical list, we can place Europe, North America, Australia and New Zealand in the areas where fermented products are produced mainly using defined starter cultures, while Asia and Africa are extraordinary ambassadors of spontaneous fermentation [40,49].…”
Section: Industrial and Artisan Fermentations 21 Microbiology Of Fementioning
confidence: 99%
“…Moreover, traditional food fermentation processes can be broadly classified into (a) lactic acid fermentation, (b) fungal fermentation and (c) alkaline fermentation [15,19,[49][50][51]. Examples of lactic acid fermented products, i.e., products primarily fermented by lactic acid bacteria, include yoghurt, sausages, cheese, sauerkraut (fermented cabbage from eastern and central Europe), kimchi (fermented and spiced Napa cabbage from Korea) [15,19] and soy sauce (ganjang) [52].…”
Section: Industrial and Artisan Fermentations 21 Microbiology Of Fementioning
confidence: 99%
See 1 more Smart Citation